Dysregulated circRNA_100876 suppresses proliferation of osteosarcoma cancer cells by targeting microRNA‐136. Issue 9 (8th May 2019) - Jin, Jian; Chen, Ajuan; Qiu, Weizheng; Chen, Yilin; Li, Qingchu; Zhou, Xinying; Jin, Dadi
Abstract: The aim of this study was to explore the regulatory mechanism of circRNA_100876/ microRNA‐136 (miR‐136) axis in the development and progression of osteosarcoma cancer. Quantitative real‐time polymerase chain reaction (RT‐qPCR) was used to evaluate the expression levels of circRNA_100876 and miR‐136 in osteosarcoma cancer samples and the adjacent nontumor tissues. Then, cell proliferation, cell cycle, apoptosis, and migration of circRNA_100876‐knocked down cells were analyzed by in vitro and in vivo experiments, using cell counting kit‐8 (CCK‐8), flow cytometry, and transwell and tumorigenesis assays. The expression of circRNA_100876 was found to be significantly upregulated in osteosarcoma, and was closely correlated with the tumor size and tumor differentiation degree. In addition, the knockdown of circRNA_100876 could significantly inhibit the tumor growth, both in vitro and in vivo. Flow cytometry and Western blot analysis results showed that the downregulation of circRNA_100876 inhibited osteosarcoma cells proliferation via promoting apoptosis and arresting more cells in the G2/M stage, as suggested by the expression of apoptosis and cell cycle pathway‐related proteins, which changed consistently. Furthermore, the level of miR‐136 was negatively correlated with the expression of circRNA_100876, and miR‐136 inhibitors were able to reverse the suppression of cell proliferation induced by silencing circRNA_100876. Our study demonstrates that the dysregulation of circRNA_100876 could induce apoptosis and arrest the cell cycle at G2/M stage, followed by suppression of cell proliferation in osteosarcoma, while silencing miR‐136 could restore the cell growth. Therefore, circRNA_100876 might serve as a promising biomarker and treatment target for osteosarcoma. Abstract : The dysregulation of circRNA_100876 could induce cell apoptosis and arrest the cells cycle at G2/M stage, followed by suppress the cell proliferation in osteosarcoma cancer, while this anticell proliferation effect could be reversed by miR‐136 inhibitors. Therefore, circRNA_100876 might serve as a promising biomarker and target treatment for osteosarcoma.